Asthma and Chronic Rhinosinusitis with Nasal Polyps: Exploring Common Pathways and Treatment Approaches - Khabibullayev T.U. (Scholars Digest Publishing, 2023)
Bronchial asthma (BA) is a chronic airway inflammatory disease characterized by the influx of cells, such as lymphocytes, eosinophils, and mast cells and, in a subgroup of patients, of neutrophils, in the bronchial wall [1,2]. The chronic inflammatory process leads to so-called airway remodeling [3]. Asthma is a variable condition in terms of clinical presentations (phenotypes) and distinct underpin pathophysiological mechanisms (endotypes). In fact, based on the biological mechanisms underlining the disease, asthma can be classified as a type 2 (eosinophilic) or non-type 2 (non-eosinophilic) endotype [4,5]. The endotypes referred to as “type 2 disease” are represented by an allergic variant either with or without eosinophilia and by the eosinophilic endotype without allergy [6,7]. In type 2 asthma endotypes, the biological mechanism involved in the inflammatory process is driven by T helper type 2 (Th2) cells, type 2 innate lymphoid cells (ILC2) and type 2 cytokines, including interleukin (IL)-4, IL-5, IL-9 and IL-13 [8]. Biomarkers, such as absolute eosinophil count in peripheral blood, total and specific IgE, and fractional exhaled nitric oxide (FeNO), may be used as indicators of type 2 asthma endotypes and help predict response to biologic therapies, now available for this variant
Keywords: bronchial asthma, nasal polyps, chronic rhinosinusitis, inflammation.